Mulheres na física: representações sociais de licenciandos e docentes em física no Brasil - Fernandes, Rubia De Fatima Antunes Martins [UNIFESP] (2020)
Although female participation has grown in many areas of science, in physics it is still quite scarce. Through studies on gender and science, it has been possible to focus on the study of institutional barriers, with explicit prohibitions on the admission of women into scientific and ideological environments, with theories and stereotypes supporting women's intellectual inferiority, which still move women away from the sciences. This master thesis aimed at identifying the possible social representation of the term 'scientist' and 'female scientist' among teachers and future physics teachers from all regions of Brazil, creating a Vergès quadrant for each of the terms. Data collection was carried out through a questionnaire based on the structural approach, using free word association as a technique to list the terms. The data processing was carried out through the EVOCATION 2005 software, which provides four quadrants where we can locate the probable central core and peripheral system of the social representation. In a complementary way, we performed the similarity analysis through the IRAMUTEQ software to give more support to the terms found for the central core. We believe that this kind of research is important with (future) teachers since, in classrooms, they can propagate their discourses directly or indirectly , and it is a scenario that can contribute to the perpetuation of the androcentric pattern of sciences and the maintenance of the dynamics established between genders.